Biomimetic aquatic surface robot for oil-spill cleanup [electronic resource] - Gotte, Augustine John, 1990- , author (2013)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Mekatronik)) - Universiti Teknologi Malaysia, 2013